Trends of Childhood Obesity in China and Associated Factors. (April 2015) - Sun, Guiju; Jia, Genmei; Peng, Honglei; Dickerman, Barbra; Compher, Charlene; Liu, Jianghong
Childhood obesity is worsening at dramatic rates and has become a public health crisis. This study investigated these trends in childhood obesity and examined parental factors that may contribute to overweight and obesity. Body mass index (BMI) was calculated from height and weight measurements taken annually from 2004 to 2007 in a subsample of 136 children (2-4 years old), from the Jintan Child Health Project in China. Parental factors were assessed through a self-administered questionnaire. Prevalence rates of overweight and obesity rose from 6.6% and 2.2% in 2004 to 15.4% and 6.6% in 2007 ( p < .05). Overweight was significantly associated with maternal employment ( p < .05), but not with parental education level, maternal age at birth, or breast-feeding. To counter this rapid increase of obesity and overweight prevalence, nurses should regularly monitor children's weight and advise parents, especially working mothers, on the nutritional benefits of home-cooked meals.